Biotic and abiotic controls on body size during critical life history stages of a pelagic fish, Pacific herring (Clupea pallasii). (22nd March 2013) - Reum, Jonathan C. P.; Essington, Timothy E.; Greene, Correigh M.; Rice, Casimir A.; Polte, Patrick; Fresh, Kurt L.
Abstract Variation in growth and body size during critical life history stages can have important implications for life history schedules and survivorship. For Pacific herring (Clupea pallasii), there is still debate as to whether juvenile body size is governed by density‐dependent or ‐independent processes and few have evaluated whether the relative importance of either process shifts over the course of early ontogeny. We used a unique data set consisting of seasonal measurements of abundance, body size, and spatial distribution within a semi‐enclosed basin of Puget Sound (Washington State, U.S.A.) to measure the relative importance of temperature and cohort abundance on body size at distinct time periods, and evaluated whether density‐dependent habitat shifts might be responsible for density‐dependent growth. Over the 9 years of sampling (2001–2010) midsummer body size was positively related to temperatures experienced during the egg/yolk sac and larval stages and unrelated to cohort abundance. However, fall body size was negatively correlated with abundance and uncorrelated with both midsummer body size and temperature, indicating a shift from density‐independent to density‐dependent control over the course of the growing season. Thus, density‐dependent effects may supplant density‐independent effects exhibited early in herring life history. Our data on spatial distributions of herring and their zooplankton prey indicate that density‐dependent reductions in growth may be explained by density‐dependent habitat shifts that lead to reduce overlap of herring with zooplankton. Evidence of density‐dependent growth in marine fish populations is often attributed to exploitative competition, but our results suggest that these patterns may partly be mediated by density‐dependent distribution expansions in to prey‐poor habitat.